Challenges Faced by Academic Researchers in Homoeopathic Institutions: A Critical Appraisal and Recommendations for Advancement (Homoeopathy for All, 2025)
Academic research is fundamental  to the progression of medical  sciences, including homoeopathy.  Despite its recognized importance,  homoeopathic institutions  encounter distinctive challenges  that impede the cultivation of a  robust research culture. This paper  systematically analyzes the barriers  faced by academic researchers  in homoeopathic institutions,  categorizing them into institutional,  regulatory, infrastructural, and  personal domains.  Key barriers include lack of  strategic vision, insufficient faculty  training, limited funding, restricted  data access, and inadequate research  incentives. Recommendations are proposed  to address these challenges and  foster an environment conducive  to high-quality scientific inquiry  and innovation. A comprehensive  multi-tiered approach is essential  to promote scientific rigor and  innovation in homoeopathic  academia.
Keywords: Academic; research; fundamental; progression